The Effect of Counseling About Implants Contraception Using Flip Chart Media on The Anxiety Level of Prospective Acceptors - Rashel, Salsabila Nuriliyah Rashel; Alfiah, Siti; Setiyani, Astuti; Septianti Purwanto, Triana (Jurnal Ilmiah Kesehatan, 2025)
The contraceptive method that dominates the choices of couples of childbearing age (PUS) in the city of Surabaya in 2022 is the Non-Long-Term Contraceptive Method (Non-MKJP) compared to the Long-Term Contraceptive Method (MKJP). The low number of acceptors of contraceptive implants is due to the anxiety level of potential acceptors. This research aimed to determine the effect of implant contraceptive counselling using flip charts on the anxiety level of potential acceptors. This research is pre-experimental design research. We used a purposive sampling technique to select the sample, which included 15 respondents. The independent variable was counselling on contraceptive implants using flip chart media, while the dependent variable was anxiety of potential acceptors. Data collection used the Hamilton Anxiety Rating Scale (HARS) questionnaire. The Wilcoxon Signed Ranks Test was used to analyse the presence of influence with a significance value of <0.05. The results of the study showed that the anxiety level of prospective acceptors before being given intervention, the majority (73.3%) of respondents had a mild level of anxiety after being given the intervention, with almost all (93.3%) of respondents having no anxiety. From the results of the analysis, the result was 0.001, which means <0.05, so it can be concluded that there is an influence of implant contraceptive counselling using flip chart media on the anxiety level of potential acceptors. Based on the description above, it can be concluded that there is an influence of implant contraceptive counselling using flip chart media on the anxiety level of prospective acceptors.